2021
DOI: 10.1007/s00330-020-07597-9
|View full text |Cite
|
Sign up to set email alerts
|

CT-like images based on T1 spoiled gradient-echo and ultra-short echo time MRI sequences for the assessment of vertebral fractures and degenerative bone changes of the spine

Abstract: Objectives To evaluate the performance of 3D T1w spoiled gradient-echo (T1SGRE) and ultra-short echo time (UTE) MRI sequences for the detection and assessment of vertebral fractures and degenerative bone changes compared with conventional CT. Methods Fractures (n = 44) and degenerative changes (n = 60 spinal segments) were evaluated in 30 patients (65 ± 14 years, 18 women) on CT and 3-T MRI, including CT-like images derived from T1SGRE and UTE. Two radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 38 publications
1
74
0
Order By: Relevance
“…4 Recent studies suggested the use of UTE and zero TE (ZTE) sequences for the depiction of cortical and trabecular bone. [5][6][7] It was further shown that UTE imaging enables the morphological assessment of fractures and degenerative bone changes in the spine 8,9 and joints. 10,11 In addition, susceptibility-weighted imaging (SWI), a technique that uses the different magnetic susceptibilities of tissues, is sensitive to tissues that distort the magnetic field by means of paramagnetic or diamagnetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent studies suggested the use of UTE and zero TE (ZTE) sequences for the depiction of cortical and trabecular bone. [5][6][7] It was further shown that UTE imaging enables the morphological assessment of fractures and degenerative bone changes in the spine 8,9 and joints. 10,11 In addition, susceptibility-weighted imaging (SWI), a technique that uses the different magnetic susceptibilities of tissues, is sensitive to tissues that distort the magnetic field by means of paramagnetic or diamagnetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, results and conclusions are only applicable to the vendor-specific dualsource DECT technique and post-processing software, as well as to the employed imaging protocols, which are routinely used in our department in case of spinal trauma. Particularly in the assessment of fracture lines, alternative MRI protocols could have performed differently, for instance by using diverse slice thickness or sequences such as T1 spoiled gradient-echo or ultra-short echo time sequences, which have recently been shown to provide image quality comparable to CT for the evaluation of certain bone pathologies of the spine [30].…”
Section: Discussionmentioning
confidence: 99%
“…When acquired in 3D, gradient echo imaging can provide "CT-like" high bone-to-soft tissue contrast images with high spatial resolution. 6,7 Zero echo time imaging (ZTE) is a gradient echo sequence that has been applied for bone imaging (►Fig. 2).…”
Section: Gradient Echo Bone Imagingmentioning
confidence: 99%
“…The 3D T1-weighted spoiled gradient-recalled sequences of the lumbar spine acquired at 3 T that were inverted to resemble CT were 97% accurate for fracture detection with substantial to excellent agreement for degenerative findings compared with CT. 6 MR images that even more closely approximate CT can be generated from 3D T1-weighted gradient echo sequences using an image synthesis method based on deep learning (DL). A recent study examining the sacroiliac joints in patients with suspected spondyloarthritis showed that synthetic CT images were more accurate than conventional T1-weighted 2D sequences for detection of erosions, sclerosis, and ankylosis.…”
Section: Gradient Echo Bone Imagingmentioning
confidence: 99%
See 1 more Smart Citation